Pemanfaatan Teknik Kriopreservasi dalam Penyimpanan Plasma Nutfah Tanaman - Ika Roostika; Ika Mariska (Buletin Plasma Nutfah, 2003)
AbstractThe two basic approaches for conservation of plant genetic resources are ex situ and in situ conservation. Cryopreservation is a potential method for long term preservation of plant germplasm. Cryopreservation technique could be used to preserve plant materials with unlimited time (until 20 years) because it bring the materials to metabolically inactive state and completely arrest the growth in liquid nitrogen at –196oC. This method is more efficient in terms of cost, time, space, and labour because it does not require frequenlty subculture. Cryopreservation techniques can be divided in to classical technique and new techniques. Classical technique can be applied to limited species but new techniques can be applied to wide range of species and many types of explant. The success of cryopreservation is not only indicated by the high rate of survival and regenerated culture, but also on the stability level of culture after cryopreservation.AbstrakPenyimpanan plasma nutfah dapat dilakukan secara ex situ dan in situ. Teknik kriopreservasi merupakan teknik penyimpanan jangka panjang. Dalam hal ini, bahan tanaman disimpan di dalam nitrogen cair yang mempunyai suhu -196oC. Pada suhu tersebut, bahan tanaman hampir sama sekali tidak mengalami proses metabolisme sehingga masa penyimpanan menjadi tidak terbatas (hingga 20 tahun). Penyimpanan dengan cara tersebut tidak memerlukan tindakan subkultur yang berulangulang sehingga lebih efisien dari segi biaya, waktu, ruang penyimpanan, dan tenaga. Teknik kriopreservasi dibedakan atas teknik lama dan teknik baru. Teknik lama hanya dapat diterapkan pada spesies tertentu, sedangkan teknik baru dapat diterapkan pada skala spesies yang lebih luas dan jenis eksplan yang lebih banyak. Keberhasilan teknik kriopreservasi tidak hanya ditunjukkan oleh kemampuan hidup dan regenerasi bahan tanaman pasca kriopreservasi tetapi juga ditentukan oleh tingkat stabilitas genetiknya.